Clotted blood samples in the neonatal intensive care unit: A retrospective, observational study to evaluate interventions to reduce blood sample clotting - Matheus F. P. T. van Rens (17993767) (2023)
Background Blood draws for laboratory investigations are essential for patient management in neonatal intensive care units (NICU). When blood samples clot before analysis, they are rejected, which delays treatment decisions and necessitates repeated sampling. Aims To decrease the incidence of rejected blood samples taken for laboratory investigation as a result of clotted sample. Study design This retrospective observational study used routine data on blood draws from preterm infants collected between January 2017 and June 2019 in a 112‐cot NICU in Qatar. Quality improvement interventions to reduce the rate of clotted blood samples included: awareness raising and safe sampling workshops with NICU staff, involvement of the neonatal vascular access team, development of a complete blood count (CBC) sample collection pathway, review of sample collection equipment, introducing the Tenderfoot® heel lance, establishment of benchmarks and provision of dedicated blood extraction equipment. Results First attempt blood draw occurred in 10 706 cases, representing a 96.2% success rate. In 427 (3.8%) cases, the samples were clotted requiring repeat collection. The overall rate of clotted specimens decreased from 4.8% in 2017 and 2018 to 2.4% in 2019, with odds ratios of 1.42 (95% confidence interval [CI] 1.13–1.78, p = .002), 1.46 (95% CI 1.17–1.81, p < .001) and 0.49 (95% CI 0.39–0.63, p < .001), respectively. The majority (87%–95%) of blood samples were by venepuncture using an intravenous (IV) catheter or the NeoSafe™ blood sampling device. Heel prick sampling was the second (2%–9%) most common method. Clotted samples were most frequently associated with needle use, 228 of 427 (53%), and IV cannula, 162 of 427 (38%), with odds ratios of 4.14 (95% CI 3.34–5.13, p < .001) and 3.11 (95% CI 2.51–3.86, p < .001), respectively. Conclusions Our interventions over 3 years were associated with reduced rates of sample rejection due to clotting, and this led to improved patient experience through fewer repeated samplings. Relevance to Clinical Practice The insights gained from this project can help to improve patient care. Interventions that reduce the rate of blood sample rejection by clinical laboratories can lead to economic savings, timelier diagnostic and treatment decisions, and contribute to an improved quality care experience for all critical care patients, irrespective of age, by reducing the need for repeated phlebotomy and the risk of related complications. Other Information Published in: Nursing in Critical Care License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/nicc.12941